Teacher Professional Development beyond the pandemic: A Delphi study on the potential of the concept of learning ecologies - Guàrdia Ortiz, Lourdes (2022)
Teacher training for the effective implementation of Information and Communication Technologies (ICT) in education has become a key aspect of educational research. In this regard, the lack of appropriate models to support teachers in their professional development is evident. An investigation has been conducted on the most effective ways in which elementary school teachers acquire their digital competencies based on the contributions of 23 experts. Using Delphi methodology with two iterations, expert knowledge about the problem was probed to learn how it is developed and refined. Adopting the theoretical lens of Learning Ecologies, the results provide a contrast on which components support effective professional learning with respect to ICT integration, laying the groundwork for new methods and approaches to professional development.